A GP effort estimation model utilizing line of code and methodology for NASA software projects - Alaa, F. Sheta; Al-Afeef, Alaa (2010 10th International Conference on Intelligent Systems Design and Applications, 2010)
There is still an urgent need of finding a mathematical model which can provide an accurate relationship between the software project effort/cost and the cost drivers. A powerful algorithm which can optimize such a relationship via developing a mathematical relationship between model variables is urgently needed. In this paper, we explore the use of GP to develop a software cost estimation model utilizing the effect of both the developed line of code and the used methodology during the development. An application of estimating the effort for some NASA software projects is introduced. The performance of the developed Genetic Programming (GP) based model was tested and compared to known models in the literature. The developed GP model was able to provide good estimation capabilities compared to other models.
Keywords: dept.csc